1995
DOI: 10.1007/bf02246548
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation between cognitive and motor/motivational deficits in the delayed matching to position test: effects of scopolamine, 8-OH-DPAT and EAA antagonists

Abstract: The effects of the muscarinic antagonists scopolamine HBr and MeBr, the 5-HT1A agonist 8-hydroxy-2-(di-n-propylamino)tetralin (8-OH-DPAT), and the N-methyl-d-aspartate (NMDA) antagonists MK-801 and CGS-19755 on performance of rats in a delayed matching-to-position task were examined. Pretreatment with scopolamine HBr (0.05 and 0.1 mg/kg), resulted in a delay-dependent decrease in the percentage of correct responses and discriminability (log d), but had no effect on either the latency to complete trials, or the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
2

Year Published

1996
1996
2008
2008

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(45 citation statements)
references
References 40 publications
4
39
2
Order By: Relevance
“…Results showed that the increase in locomotor activity is due to the central effect of the drug, because scopolamine MeBr does not cross the blood-brain barrier, unlike scopolamine HBr. This is in parallel with the observed effects of scopolamine on cognitive tasks such as memory in other studies (36)(37)(38)(39)(40)(41)(42). In these studies, scopolamine HBr was found to affect NEUROSCIENCE RESEARCH COMMUNICATIONS, VOL.…”
Section: Drugssupporting
confidence: 68%
“…Results showed that the increase in locomotor activity is due to the central effect of the drug, because scopolamine MeBr does not cross the blood-brain barrier, unlike scopolamine HBr. This is in parallel with the observed effects of scopolamine on cognitive tasks such as memory in other studies (36)(37)(38)(39)(40)(41)(42). In these studies, scopolamine HBr was found to affect NEUROSCIENCE RESEARCH COMMUNICATIONS, VOL.…”
Section: Drugssupporting
confidence: 68%
“…Our findings, too, suggest that the effects of scopolamine may not be confined to working memory, in that the most effective dose (0.06 mg/kg SC) disrupted all measures of performance, not just the highest delay attained. interestingly, Stanhope, McLenachan, and Dourish (1995) found that low doses of scopolamine (0.05 and 0.1 mg/kg iP) produced delay-dependent reductions in the accuracy of rats performing a DMTS task without reducing the number of trials completed. This finding is suggestive of selective impairment of working memory.…”
Section: Discussionmentioning
confidence: 95%
“…Here, this possibility had been reduced by requiring the subjects to press a centrally located lever to activate the availability of a choice (illumination of both magazine lights), thus ensuring that the mouse would always be in the same location when the choice was presented. Furthermore, the installation of partition walls between the lever and magazines also reduced the use of simple motor pattern as mediating strategy, although this possibility can never be completely eliminated (see Stanhope et al 1995). Most critically, however, the use of mediating behaviour is expected to assist performance at short rather than at long delays (Rawlins and Tsaltas 1983).…”
Section: Discussionmentioning
confidence: 99%